(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the emotional concept of "envy" as expressed in Uzbek and Korean languages from a cross-cultural perspective. The study analyzes the linguo-pragmatic features of the concept, its cultural and social perception within both societies, and how it is reflected through language. The research compares both the negative and relatively positive connotations of envy and examines its representation in oral and written discourse. Through the analysis of paremias, idiomatic expressions, and synonymous layers in both languages, the article highlights the cultural attitudes toward envy and identifies both commonalities and cultural distinctions. This cross-cultural approach offers deeper insight into the interconnection between language and culture and emphasizes the value of pragmatics and cultural linguistics in conceptual analysis.